ENDOMETRIAL CHANGES IN WOMEN ON TAMOXIFEN FOR BREAST CANCER (Iraqi Journal of Medical Sciences, 2016)
Background:Tamoxifen is a selective estrogen receptor modulator (SERM) that is widely used in the treatment of patients with breast cancer and for chemoprophylaxis in high risk women. Tamoxifen results in a spectrum of endometrial changes due to it's estrogenic effect on the endometrium.Objectives:To evaluate the extent of endometrial pathologies that might develop in postmenopausal breast cancer patients following treatment with tamoxifen.Methods:Sixty postmenapausal with breast carcinoma women were involved in this study, Thirty women were receiving 20-40 mg of tamoxifen daily for a period of 6 to 60 months constitutes the study group, and a control group included 30 postmenopausal breast carcinoma patients who were not receiving tamoxifen. Transvaginal sonography was performed for the measurements of the endometrial thickness and the presence of endometrial pathology. All the patients underwent endometrial sampling and the curetting were sent for histopathological examination.Results:There was statistically significant increase in the frequency of endometrial pathology in those on tamoxifen;there was 11 endometrial pathologies in the case group,while the control group was associated with only 3 pathologies(p=0.015). There was signi?cant difference in endometrial thickness between case group (0.73+0.32 mm) and the control group (0.5+0.16mm) with p value 0.002. Only patients with endometrial thickness of more than 5mm were associated with pathologies, 7 (38.8%) of the endometrial biopsies revealed normal endometrium, whereas, 11(61.1%) had endometrial pathology like hyperplasia, endometrial polyp or carcinoma. The rate of endometrial pathologies considerably increase with increasing duration of treatment.Conclusion:The long term use of tamoxifen as adjuvant therapy for carcinoma breast is associated with increase frequency of endometrial pathology. Endometrial thickness is increased in such patients and is related to the duration of tamoxifen use.Key Words:Tamoxifen, Endomatrial pathology, Breast cancer.
Keywords: Tamoxifen; Endomatrial pathology; Breast cancer